Credit derivatives & synthetic structures : - Tavakoli, Janet M. (Wiley, 2001)
Here is the only comprehensive source that explains the various instruments in the market, their economic value, how to document trades, and more. This new edition includes enhanced treatment of U.S. and worldwide regulatory issues, and new product structures.